Comparison between the Astaxanthin Release Profile of Mesoporous Bioactive Glass Nanoparticles (MBGNs) and Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV)/MBGN Composite Microspheres - Aguilar Rabiela, Arturo Elias; Homaeigohar, Shahin; González-Castillo, Eduin I.; Sanchez, Mirna; Boccaccini, Aldo R. (Polymers, 2023)
In recent years, composite biomaterials have attracted attention for drug delivery applications due to the possibility of combining desired properties of their components. However, some functional characteristics, such as their drug release efficiency and likely side effects, are still unexplored. In this regard, controlled tuning of the drug release kinetic via the precise design of a composite particle system is still of high importance for many biomedical applications. This objective can be properly fulfilled through the combination of different biomaterials with unequal release rates, such as mesoporous bioactive glass nanoparticles (MBGN) and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) microspheres. In this work, MBGNs and PHBV-MBGN microspheres, both loaded with Astaxanthin (ASX), were synthesised and compared in terms of ASX release kinetic, ASX entrapment efficiency, and cell viability. Moreover, the correlation of the release kinetic to phytotherapeutic efficiency and side effects was established. Interestingly, there were significant differences between the ASX release kinetic of the developed systems, and cell viability differed accordingly after 72 h. Both particle carriers effectively delivered ASX, though the composite microspheres exhibited a more prolonged release profile with sustained cytocompatibility. The release behaviour could be fine-tuned by adjusting the MBGN content in the composite particles. Comparatively, the composite particles induced a different release effect, implying their potential for sustained drug delivery applications.
CRIS-Team Scopus Importer:2023-06-23
Keywords: Astaxanthin; composite microspheres; controlled release; sustained release

Integration of mesoporous bioactive glass nanoparticles and curcumin into PHBV microspheres as biocompatible composite for drug delivery applications - Aguilar Rabiela, Arturo Elias; Leal-Egaña, Aldo; Nawaz, Qaisar; Boccaccini, Aldo R. (Molecules, 2021)
Bioactive glasses (BGs) are being increasingly considered for biomedical applications. One convenient approach to utilize BGs in tissue engineering and drug delivery involves their combination with organic biomaterials in order to form composites with enhanced biocompatibility and biodegradability. In this work, mesoporous bioactive glass nanoparticles (MBGN) have been merged with polyhydroxyalkanoate microspheres with the purpose to develop drug carriers. The composite carriers (microspheres) were loaded with curcumin as a model drug. The toxicity and delivery rate of composite microspheres were tested in vitro, reaching a curcumin loading efficiency of over 90% and an improving of biocompatibility of different concentrations of MBGN due to its administrations through the composite. The composite microspheres were tested in terms of controlled release, biocompatibility and bioactivity. Our results demonstrate that the composite microspheres can be potentially used in biomedicine due to their dual effects: bioactivity (due to the presence of MBGN) and curcumin release capability.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Bioactive glass nanoparticles; Composite microspheres; Drug delivery systems; PHBV

Thermal and tribo-mechanical properties of high-performance poly(etheretherketone)/reduced graphene oxide nanocomposite coatings prepared by electrophoretic deposition - González Castillo, Eduin Ivan; Torres, Yadir; González, Francisco J.; Aguilar Rabiela, Arturo Elias; Shuttleworth, Peter S.; Ellis, Gary J.; Boccaccini, Aldo R. (Journal of Materials Science, 2023)
The thermal stability and degradation, near-to-surface mechanical properties, and scratch resistance and damage mechanism of poly(etheretherketone) (PEEK)/reduced graphene oxide (RGO) nanocomposite coatings are analyzed and discussed in terms of their nanosheet content and microstructure. Although RGO modified the thermal stability and degradation of the polymeric matrix, for instance, by slightly reducing the onset degradation temperature, its addition was not a limiting factor in the PEEK processing. Respecting the microstructural features induced by the nanosheets, the nanocomposite coatings were found to exhibit (i) a partially exfoliated and large-scale co-continuous morphology related to RGO nanosheets whose basal planes were mainly aligned with the coating surface, (ii) a dendritic morphology of PEEK domains related to transcrystallinity, (iii) and irregular domains associated with the deposition of PEEK particles wrapped by the nanosheets. The changes provoked by RGO in the morphology and PEEK crystalline phase influenced the near-to-surface mechanical properties, scratch resistance, and scratch damage mechanism of the nanocomposite coatings. Within this context, the interlayer strength between the nanosheets in the large-scale co-continuous morphology and PEEK transcrystallinity had an important effect. Furthermore, the random-bumpy surface texture formed by the irregular PEEK domains together with the conformal cracking damage mechanism was decisive in the scratch response of the PEEK/RGO nanocomposite coatings. The comprehensive characterization carried out in this work concludes that PEEK/RGO electrophoretic coatings are suitable for a variety of applications requiring tribo-mechanical resistance. Graphical Abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-06-30